Efektivitas Model Pembelajaran Pbl Berbantuan Media Papan Nilai Tempat Bilangan Terhadap Hasil Belajar Kognitif Matematika Siswa SD - Irma Alfiana; Agnita Siska; Sri Pudjiati; Sugiyanti Sugiyanti (Journal on Education, 2024)
The aim of this research is to determine the influence of the cognitive mathematics learning outcomes of grade 2 students using the number place score board media. Experimental research was carried out at SD Negeri Jatingaleh 01 Semarang in class 2 B consisting of 12 male students and 16 female students. The results of the research prove that the application of the PBL learning model assisted by number place score board media has an effect on the cognitive mathematics learning outcomes of class 2 students and the average pretest score for students' cognitive mathematics results is 58.96 - 83.61, while the average posttest score for students' cognitive results is 86.61 . Obtained sig > 0.365 which can be interpreted that the data is normally distributed, while the posttest data obtained sig > 0.320 which can be interpreted that the data is normally distributed. It can be concluded that the pretest and posttest data are > 0.05, which means that both data are normally distributed. Based on the results of the paired sample t-test hypothesis test above, the sig (2-tailed) is 0.000, which states that the results of the paired sample t-test hypothesis are 0.000 < 0.05 so that Ho is rejected and Ha is accepted. So it can be concluded that there is a difference in the average value of students' cognitive mathematics learning outcomes before and after being given treatment using the problem based learning model assisted by the number place score board media.